Development and Validation of an Integrated Noncommunicable Disease Registry Tool - Paika, Ronika; Thakur, JS; Khurana, Dheeraj; Bhadada, Sanjay Kumar; Vijayvergiya, Rajesh; Kapoor, Rakesh; Prinja, Shankar (Archives of Clinical and Biomedical Research, 2024)
Background: Health systems in the limited-resource setting currently face a rapidly increasing burden from noncommunicable diseases (NCDs). The registries generate high quality data of diseases surveillance for estimating the disease burden and trends in population for different geographical regions. The reporting format or the registry tools are different for different registries as per the funding agency requirements. Despite of the fact that these NCD shares common risk factors, no integrated tool for data collection on NCD data is available. In the present study a practical and systematized Integrated NCD registry tool based on the international and national literature available has been developed and validated. Methods: We carried out a methodological study to examine the content validity of the patient-centered communication instrument through a two-step process (development and judgment). The Integrated NCD Registry tool for four NCDs includes the major 2 parts i.e., Part 1 includes general characteristic i.e. General data on reporting facility details, patient information, patient history including the behavioural risk factors for NCDs, Part 2 includes 4 disease modules i.e., young diabetes, Stroke, Cancer and Acute Cardiac events and follow up. For validation, at the first step, domain determination, sampling (item generation) and instrument formation and at the second step, content validity ratio, content validity index and modified kappa statistic was performed by a panel of experts. Suggestions of expert panel and item impact scores are used to examine the instrument face validity. Result: The overall S-CVI for the 126 items scale was 0.91 which indicated high content validity of the items. Items which had a 0.67 I-CVI indicated the need for revising them. Kappa statistic ranged from 0.81 to 1 for most of the items. Nine items with negative kappa coefficient reflected a disagreement among raters regarding their inclusion in the integrated registry tool. In the he final version, it was observed that out of 125 items, 92% of the items were validated. For face validity, the impact scores of all the items were above 1.5 which is acceptable. The final version of the tool includes four NCDs includes the major 2 parts i.e. Part 1 includes general characteristic i.e. General data on reporting facility details, patient information, patient history including the behavioural risk factors for NCDs, Part 2 includes 4 disease modules i.e. Young diabetes, Stroke, Cancer and Acute Cardiac events and follow up. Conclusion: The quantification of content validity on the basis of CVI (I-CVI & S-CVI), Kappa coefficient, and CVR indicated high content validity for the items. Thus, a Registry tool was constructed and validated professionals to collect the NCD patient’s data in a timely, effective and quality manner. Integrated NCD registry will offer a sustainable noncommunicable disease surveillance module for limited resource settings.